Redes pessoais significativas e maternidade em famílias monoparentais em situação de vulnerabilidade social - Machado, Mônica Sperb (2019)
Monoparental families represent an increasing number of families in Brazil, the majority formed by the mother, with no spouse, as responsible for their children. Motherhood in this context encompasses the challenges of mothers taking on the maintenance and sustenance of the home, as well as the education of their children. The situation of social vulnerability in which many are inserted makes this reality even more complex, interposing fragilities and making essential the existence of maternity support networks. Thus, the present qualitative, exploratory and descriptive study aimed to understand the dynamics of significant personal networks for the performance of motherhood in single- parent female families in the context of social vulnerability. Ten women with children, responsible for single-parent families in socially vulnerable situations, were enrolled in Social Assistance Reference Centers (CRAS) of a municipality in the interior of Rio Grande do Sul. All ethical precepts have been considered. The data were collected through a Sociodemographic Questionnaire, a semi-structured Interview and the Network Map and submitted to Content Analysis. The results were presented in the form of two scientific articles: "Meanings attributed to maternity in female single parents in social vulnerability" and "Significant personal networks of women responsible for single parents families in social vulnerability”. It was found that mothers were engaged in parental activities related to the physical, emotional, social, and intellectual care of their children, as well as investing efforts in their discipline and values education. The care and education of the children showed themselves to be linked to the meanings of motherhood attributed by the participants, being considered maternal responsibilities and permeated by peculiarities of the social context of single parenthood and vulnerability. Relatives, friends, neighbors, "bosses" and professionals/services participate in different ways in the maintenance of single parent families and as support in the maternity performance of the women responsible for them. The main functions of the links that made up the networks were: the material support, important to family survival; the social company, to share the daily routine; the emotional, to face the experiences of overload and life stories marked by frailties; the council guide, relevant to the educational aspects of the children; and social regulation, which reaffirms the roles and responsibilities of mothers towards their children. It is considered relevant to increase the knowledge about the significant personal networks, to understand that their recognition can be strategic in professional practices and contribute to the experience of motherhood of women responsible for single parents families in a situation of social vulnerability.